COMPARATIVE ASPECTS OF STUDY RESULTS OF ELECTROTECHNICIANS' PROFESSIONAL TRAINING IN GERMANY AND UKRAINE - Тетяна Ларіна (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The article presents an analytical comparison of electrotechnicians' professional training at technical colleges of Germany and Ukraine. There has been made an analysis of the content of educational and professional program of training, and formation of the mentioned above specialists' professional competence on various stages of professional training in Germany and Ukraine. Through a comparative prism the identical formats of professional competence and academic results of the future specialists have been shown in this research.